2019
DOI: 10.1002/asi.24233
|View full text |Cite
|
Sign up to set email alerts
|

Down the rabbit hole: Investigating disruption of the information encountering process

Abstract: Information encountering (IE) often occurs during active information-seeking and involves passively finding unsought, unexpected information that is subjectively considered interesting, useful or potentially useful. While the idealized IE process involves engaging with information after noticing it (e.g. by examining it, conducting follow-up seeking to determine usefulness, then using or sharing it), the process can be disrupted -resulting in missed opportunities for knowledge and insight creation. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This is analogous to their ability and willingness to notice, examine and follow-up on encountered information. She found that some participants were much less willing to “change direction” than others after encountering information – a finding supported more recently by Makri and Buckley (2019). Personality traits, specifically extroversion (Heinström, 2006; McCay-Peet et al , 2015), have been found to increase this willingness, while stress and anxiety have been found to decrease it (Heinström, 2006).…”
Section: Later Empirical Research On Serendipity In the Context Of Information Acquisitionmentioning
confidence: 83%
See 3 more Smart Citations
“…This is analogous to their ability and willingness to notice, examine and follow-up on encountered information. She found that some participants were much less willing to “change direction” than others after encountering information – a finding supported more recently by Makri and Buckley (2019). Personality traits, specifically extroversion (Heinström, 2006; McCay-Peet et al , 2015), have been found to increase this willingness, while stress and anxiety have been found to decrease it (Heinström, 2006).…”
Section: Later Empirical Research On Serendipity In the Context Of Information Acquisitionmentioning
confidence: 83%
“…This is a simple, yet powerful way of distinguishing between active and passive information acquisition and may also serve to unify terminology if adopted by the research community as a preferred term for serendipity in the context of information acquisition. We also think IE is a particularly appropriate term as it was one of the first serendipity-related terms to be created in the field of HIB (Erdelez, 1995) and is still used to frame and motivate current studies of passive information acquisition (e.g., Jiang et al, 2019;Makri and Buckley, 2019).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this form of serendipitous information acquisition often occurs during active search, this is as an unintended byproduct (Makri et al, 2014). Search environments typically support passive information encountering indirectly and incidentally; as an unexpected but often welcome distraction to the search at hand (Makri & Buckley, 2020), but a distraction nonetheless. Although recommender systems, including those that drive personalized search, now value search result novelty and diversity as well as relevance (Castelis et al,2015), search is still better suited to active seeking than passive encountering.…”
Section: The Task Perspective: Search Unfairly Favors Some Types Of Tasksmentioning
confidence: 99%